How to conduct qualitative research in social science - Liamputtong, Pranee; Edward Elgar Publishing (Northampton : Edward Elgar Publishing, 2023)
"This book offers insights into key research-based strategies that can help to alleviate global challenges faced by both individuals and groups in society. Focusing on conducting qualitative research, the chapters highlight an approach for understanding human thoughts and actions, and examining how things actually function in society. Explaining both the theoretical and practical aspects of doing qualitative research, the book uses examples from real-world research projects to emphasise how to conduct qualitative research in the social sciences. Pranee Liamputtong draws together contributions covering qualitative research in cultural and medical anthropology, sociology, gender studies, political science, criminology, demography, economic sciences, social work, and education. Each chapter discusses the essence of a discipline before examining the contribution of qualitative enquiry and then interrogating traditional qualitative research methods as well as emerging or innovative methods. This will be an invigorating read for students and scholars of the social sciences. Its combination of theoretical and practical insights will also be essential for qualitative researchers"--
Contents: Preface -- 1. Qualitative research in the social sciences: Setting the scene / Pranee Liamputtong -- 2. 'Theory' in qualitative research: A framework that synthesises existing academic advice / Louise Keogh, Natalie Jovanovski, Sarah MacLean and Richard Chenhall -- 3. Conducting qualitative research in cultural anthropology / Katie Nelson and John Forrest -- 4. Qualitative methods in medical anthropology / Richard Chenhall and Kate Senior -- 5. Qualitative research in sociology: 'seeing' social class in qualitative data / Belinda Lunnay, Kristen Foley and Paul R. Ward -- 6. Qualitative research in women's and gender studies: The 'radical focus group' as feminist praxis / Natalie Jovanovski -- 7. Qualitative research in political science / Selen A. Ercan and Ariadne Vromen -- 8. Conducting qualitative research in criminology / Max Travers -- 9. Qualitative research in demography: Marginal and marginalised / Joe Strong, Rishita Nandagiri, Sara Randall and Ernestina Coast -- 10. Qualitative methods in economic sciences / Mirjana Radović-Marković -- 11. Qualitative methods in social work / Catherine Flynn -- 12. Conducting qualitative research in education / Jennifer Gao and Radhika Chugh -- Index.
Includes bibliographical references and index.
Description based on print record.
Keywords: elektronické knihy; electronic books; Qualitative research; Social sciences -- Research